Desenvolvimento da síntese total do (±)-ácido jasmônico visando aplicação em escala industrial - Secatto, Marcelo (2013)
Jasmonic acid is a plant hormone that helps in the partition of nitrogen and acts mainly in defense against pathogens. It was first isolated in 1962 from the essential oil of Jasminum grandiflorum, but we know that it can be found in more than two hundred species of plants, including ferns, mosses and fungi. Jasmonic acid is formed biosynthetically from linolenic acid and is obtained by enzymatic steps including cyclization and reduction. It has a cyclopentanone structure with has two stereogenic centers, that gives four possible stereoisomers in the R or S absolute configuration. Natural ocurring (2R, 3R)-jasmonic acid is shown in the figure below. In the literature there is some racemic and enantioselective synthetic routes to obtain jasmonic acid and its methyl ester, characterized for having different steps, starting from chiral precursors of relevant cost and a wide range of yields. The objective of this work is the exploration of a racemic synthesis route that is summed up in a few steps aiming high yields, envisaging application in industrial scale, that encompass social trends to develop sustainable culture plantations, with reduced use of pesticides.